REDESAIN KAWASAN WISATA RAWA DESA BANYU HIRANG - Afifah, Nurkhalishah; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The condition of Hulu Sungai Utara Regency as an area dominated by wetland can be an interesting potential that is expected to attract tourists to visit. One of the areas that can be developed into a wetland tourism area is Banyu Hirang Village. But unfortunately, the utilization of the village area as a recreational tourist destination based on wetland is still lacking. The potential of the community in producing UMKM products in the form of woven handicrafts purun and water hyacinth also needs to be appreciated so that it can be one of the centers of woven handicrafts in Hulu Sungai Utara Regency. The design of this wetland tourist attraction aims to preserve and introduce to tourists about the potential and utilization of natural resources in wetland in helping the economy of the community. The method of problem solving in this design focuses on the approach of 3 aspects of wetland contextual architecture, namely visual, activity and environment with 5 principles of ecotourism development, namely conservation, knowledge, tourism, community participation, and economy. The relationship between the contextual aspects of wetland and the principle of ecotourism produces sustainable tourist areas with wetland environments, where the time order is divided into several zones, namely reception zones, service zones, transition zones, educational zones, recreation zones, culinary zones and relaxing zones. Planning each zone is expected to create a special character of wetland that can provide harmony with the surrounding natural environment.